Danos do afídeo Rhopalosiphum padi (L.) (Hemiptera: aphididae) em função da duração e do nível de infestação, em estádios iniciais de trigo - Gomes, Margarida Flores Roza (2006)
Aphids in wheat have been considered relevant pests, due to direct damages by feeding on sap from the phloem, or indirectly, by acting as vectors of viruses such as Barley yellow dwarf virus (BYDV). Recently, Rhopalosiphum padi (L.) has been observed infesting wheat fields with an increasing frequency. The knowledge on aphid management is available to other species of wheat aphids rather than R.padi. Two experiments were conducted with the objective of evaluate the effects of feeding time and infestation level of R. padi in grain yield and in the BYDV symptoms at initial stages of wheat development. The first experiment was carried out in the field using a completely randomized design with split and 4 replications. The main plot was the feeding time (2 and 7 days) and the sub-plot the infestation levels (0, 2 and 10 aphids/plant). The experimental units were plots of wheat cv. Embrapa 16 at the seedling stage. The second experiment was conducted in greenhouse, in a completely randomized design with 5 replications. The factors were feeding time (2 and 10 days) and infestation levels (0, 2, 7 and 12 aphids/plant) at the seedling and tillering stages. The results showed that the feeding action of R. padi on wheat resulted in yield losses. Wheat plants at seedling stage were more prone to damage at tillering stage. The damage was proportional to feeding time and infestation levels. The effect of the duration of the infestation depended on the development stage of the plants. Yellowing of leaves also varied with the duration and the infestation level. The yield components affected were number of heads/plant, number of grain/head and number of tiller/plant. Plant height, root and canopy dry matter were also affected